Massive de-gloving thigh injury treated by vacuum therapy, dermal regeneration matrix and lipografting - Mario Cherubino; Stefano Scamoni; Igor Pellegatta; Francesca Maggiulli; Anna Minuti; Luigi Valdatta (Wolters Kluwer Medknow Publications, 2013)
Frequently lower limb injuries are caused by road and work accidents. The young age of those affected coupled with the anatomical and functional peculiarities of this part of the body with regards to social life during adolescence make the treatment of the leg wound complex and challenging. We present two cases of young girls, victims of serious road accidents who were treated initially with frequent wound washings, vacuum therapy to stimulate granulation tissue, then dermal regeneration matrix (INTEGRA ® ) and split-thickness skin grafts. After one year, both patients treated with lipofilling have shown improved cosmetic results allowing a new social life.